2014
DOI: 10.3346/jkms.2014.29.6.782
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Difference between Familial and Sporadic Ankylosing Spondylitis in Korean Patients

Abstract: Clustered occurrences of ankylosing spondylitis (AS) in family have been noticed. We evaluated patients with AS confirmed by the modified New York criteria for familial history of AS (one or more first to third degree relatives). The clinical characteristics and the recurrence risks (number of AS patients/number of familial members) of the familial AS compared to sporadic AS were investigated. Out of a total of 204 AS patients, 38 patients (18.6%) reported that they had a familial history of AS. The recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…As expected, patients with familial AS had a higher frequency of HLA–B27 positivity but lower erythrocyte sedimentation rates and C‐reactive protein levels than those with sporadic‐onset AS. Age at onset, radiographic severity, and extraarticular manifestations were similar in the 2 groups . A family history of AS was reported by 20% of patients in the National Spondyloarthropathies Registry of the Spanish Society of Rheumatology (REGISPONSER) .…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…As expected, patients with familial AS had a higher frequency of HLA–B27 positivity but lower erythrocyte sedimentation rates and C‐reactive protein levels than those with sporadic‐onset AS. Age at onset, radiographic severity, and extraarticular manifestations were similar in the 2 groups . A family history of AS was reported by 20% of patients in the National Spondyloarthropathies Registry of the Spanish Society of Rheumatology (REGISPONSER) .…”
mentioning
confidence: 82%
“…However, they reported a higher predominance of females and increased HLA–B27 positivity in patients with familial AS than in those with sporadic‐onset AS . Another study showed that 18.6% of Korean AS patients have a family history of AS . As expected, patients with familial AS had a higher frequency of HLA–B27 positivity but lower erythrocyte sedimentation rates and C‐reactive protein levels than those with sporadic‐onset AS.…”
mentioning
confidence: 85%
“…Factors described as associated with familial disease differed between studies, except for a higher prevalence of HLA-B27 identified in most of them (Almodóvar et al, 2011(Almodóvar et al, , 2016Joshi et al, 2012;Kim et al, 2014). There was also a trend to a milder disease in familial forms (Calin et al, 1993;Almodóvar et al, 2016), which might have been caused by a selection bias among familial cases (the probability to diagnose a patient with mild symptoms might be higher in the presence of a family history of SpA).…”
Section: Is There Any Phenotypic Difference Between Familial and Sporadic Spa?mentioning
confidence: 99%
“…Остеопороз у больных со стажем АС более 20 лет способствует образованию спондилофрактур, которые тесно связаны с изме-нениями биомеханических свойств позвоночного столба и нарушениями его статико-динамической нагрузки [12]. Снижение минеральной плотности кости выявляют у 10-20 % от числа обследован-ных с ЮАС [2], что в большей степени характерно для пациентов с наследственной предрасположен-ностью к заболеванию [25]. Остеодефицит при АС сопровождается высокими уровнями в крови осте-оассоциированных паратирина (паратиреоидного гормона), белков остеокальцина и остеопонтина, а также активности щелочной фосфатазы [31].…”
unclassified